Efektivitas Pembayaran Digital: Keunggulan, Tantangan, dan Solusi - Fahma Azka, Via; Talitha Azhari; Ainul Sufarhan; Aan Ansori (CV. ITTC INDONESIA, 2024)
Digital payments have become one of the important elements in the era of digital transformation, providing various benefits such as convenience, efficiency, and high security. This study aims to evaluate the effectiveness of digital payment systems by identifying advantages, challenges, and solutions that can be applied. The research method uses a descriptive qualitative approach with a literature study design, relying on secondary data from journal articles, official reports, and other trusted sources. The results of the study show that digital payments offer advantages such as easier, safer, faster, and more flexible transactions, and support the non-cash movement. However, challenges such as limited internet access, inequality in smartphone ownership, and lack of understanding of technology are still major obstacles. This study also provides various recommendations, including public education, infrastructure development, incentives for merchants, and improving system security. With the right strategy, digital payment systems can be the main solution in supporting the growth of the digital economy in Indonesia.